Nepal’s Geostrategic Location: Realist Imperatives on Foreign Policy - Paudel, Santosh Kumar (International Research Journal of MMC, 2024)
Realist imperatives in foreign policy emphasize the pursuit of national interests, power balance, and pragmatic decision-making in an anarchic international system. This study aims to analyze Nepal's foreign policy through a realist perspective, focusing on its historical evolution, challenges, and opportunities. An exploratory research design is employed, using secondary data from peer-reviewed journals, historical records, academic books, policy reports, and governmental publications. The publication period of the sources ranges between 1963 and 2023. The study finds that Nepal’s foreign policy decisions are significantly influenced by its geopolitical position and the need to balance relationships with neighboring powers India and China. The implication of this study is that realist theory provides a valuable framework for understanding how small states like Nepal navigate complex international dynamics to safeguard their national interests.